THE CORRELATION AMONG THE FOURTH SEMESTER STUDENTS’ PERSONALITY TYPES, LEARNING STYLES, AND WRITING ACHIEVEMENT OF ENGLISH EDUCATION STUDY PROGRAM OF PGRI UNIVERSITY OF PALEMBANG - Hermansyah. K (ELTE Journal (English Languange Teaching and Education), 2014)
Abstract   The purposes of this study were to find: (1) the most personality type was employed by the fourth semester students of English Education Study program at PGRI University of Palembang (2) the most learning style was employed by the fourth semester students’ of English Education Study Program at PGRI University of Palembang, (3) whether or not the fourth semester students’ personality types of correlate significantly with their writing achievement, (4) whether or not the fourth semester students’ learning styles correlate significantly with their writing achievement, (5) whether or not the fourth semester students’ learning styles correlate significantly with their writing achievement, and (6) whether or not the fourth semester students’ personality types and learning styles contribute to their writing achievement; The population of this study was the Fourth semester students of English Education Study Program of PGRI University of Palembang in academic year of 2013/2014 consisting 231 students. From the population, 75 students were taken as his research sample. Then, the writer distributed two questionnaires for knowing students personality types and learning styles, and a writing achievement test for knowing students writing achievement.  Statistical analysis of Pearson Product Moment Correlation Coefficient was used to investigate whether there was a significant correlation between students’ personality types on students’ writing achievement, then learning styles on students’ writing achievement. Key Words: Correlation, Personality Types, Learning Styles, Writing                   Achievement.